Impact of Bilateral Trade Agreement and Custom Procedures on The Indo-Srilankan Textile Supply Chain - Lakhtarwala, Husain Aliasgar (2012)
This paper aims to identify the bilateral trade agreements its procedures and custom procedures and its impact on the Indo-Srilanka Textile Supply Chain. To investigate the different compliance procedures and the formalities to be undertaken by the exporters and importers of INDIA-SRILANKA trading garments and textile products between them for which we have used a Surveys and Interviews conducted in 2012. The findings put light in the bilateral trade and problems traders face while exporting products between India-Srilanka. In our analysis we have discussed ISFTA, SAFTA and the CEPA and their effect trade of textile and clothing between India-Srilanka. We have also analysed how trade barrier both tariff and non tariff affect the textile supply chain leading to informal trade. How this affects the industry as a whole and how companies are trying to overcome these procedures and formalities to have a successful trade link with each other. We analyse how Trade facilitation plays an important role in the development of Indo-Srilankan textile supply chain eliminating trade obstacles faced by Srilankan exporters with India further discussing the measures taken by Indian India to facilitate trade with Srilanka.